2019
DOI: 10.1038/s41598-019-41936-1
|View full text |Cite
|
Sign up to set email alerts
|

Genomic insights into HSFs as candidate genes for high-temperature stress adaptation and gene editing with minimal off-target effects in flax

Abstract: Flax ( Linum usitatissimum ) is a cool season crop commercially cultivated for seed oil and stem fibre production. A comprehensive characterization of the heat shock factor ( HSF ) candidate genes in flax can accelerate genetic improvement and adaptive breeding for high temperature stress tolerance. We report the genome-wide identification of 34 putative HSF genes from the flax genome, which we mapped on 14 of the 15 ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 64 publications
0
19
0
Order By: Relevance
“…Previous studies have shown that transcription activation in vivo requires HSEs in HSF protein binding. The HSF recognizes a typical 5 bp sequence, 5-nGAAn-3, which forms at least three contiguous inverted repeats in the downstream HSP promoter ( Saha et al, 2019 ). The highly conserved DNA-binding domain (DBD) in the N-terminus includes one three-helical bundle (α1, α2, α3) and one antiparallel four-stranded β -sheet ( β 1, β 2, β 3, β 4) to form a helix-turn-helix structure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that transcription activation in vivo requires HSEs in HSF protein binding. The HSF recognizes a typical 5 bp sequence, 5-nGAAn-3, which forms at least three contiguous inverted repeats in the downstream HSP promoter ( Saha et al, 2019 ). The highly conserved DNA-binding domain (DBD) in the N-terminus includes one three-helical bundle (α1, α2, α3) and one antiparallel four-stranded β -sheet ( β 1, β 2, β 3, β 4) to form a helix-turn-helix structure.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, HSF gene families were analyzed in different species, including maize, rice, pepper, tomato, soybean, and flax. Genome-wide analysis indicated that HSF proteins in various species may have different functions in reducing damage to high-temperature stress and also provide resources for evolutionary analysis ( Guo et al, 2015 ; Saha et al, 2019 ; Yang et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…The promoter regions of the soybean HSFs contained cis-elements that likely participate in drought, low temperature, and ABA stress responses. GmHsp90A2, GmRAR1, GmSGT1, GmSBH1P, and GmSBH1 are essential chaperones of the protective stress response in soybean (Chen et al, 2019 ; Huang et al, 2019b ), while LusHSF responds in linseed (Saha et al, 2019 ). These regulators play their role in making the interaction between the MBF1c ethylene activated pathway and HSP allied signaling.…”
Section: Heat Stress Sensing and Signalingmentioning
confidence: 99%
“…Scaffold-level genome assemblies of linseed cultivar Longya-10, fiber cultivar Heiya-14, and pale flax were generated in 2020, based on Illumina sequencing, Hi-C technology, and genetic mapping (Zhang et al, 2020b ). These results are extremely important for further progress in molecular studies of flax, the development of genome editing, and marker-assisted and genomic selection (Saha et al, 2019 ; Morello et al, 2020 ; You and Cloutier, 2020 ). A high-quality genome can be used as a reference for genome and transcriptome assemblies of different flax cultivars/lines, and the identification of polymorphisms and differences in gene expression within L. usitatissimum genotypes (Dmitriev et al, 2019 , 2020b ; Guo et al, 2019 ; Wu et al, 2019 ).…”
Section: Introductionmentioning
confidence: 97%